Does Female Directorship on Independent Audit Committees Constrain Earnings Management? - Sun, Jerry (Journal of business ethics, 2011)
This study examines whether the gender of the directors on fully independent audit committees affects the ability of the committees in constraining earnings management and thus their effectiveness in overseeing the financial reporting process. Using a sample of 525 firm-year observations over the period 2003 to 2005, we are unable to identify an association between the proportion of female directors on audit committees and the extent of earnings management.